2006
DOI: 10.1080/10826060500533976
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Pancreatic Lipase on Chitin and Chitosan

Abstract: In this study, porcine pancreatic lipase (EC 3.1.1.3) was immobilized on chitin and chitosan by adsorption and subsequent crosslinking with glutaraldehyde, which was added before (conjugation) or after (crosslinking) washing unbound proteins. Conjugation proved to be the better method for both supports. The properties of free and immobilized enzymes were also investigated and compared. The results showed that the pH optimum was shifted from 8.5 to 9.0 for both the immobilized enzymes. Also, the optimum tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Before immobilization, 0.01 g of support was equilibrated in 3 mL of 0.05 M phosphate buffer (pH 7) for 20 min at 25C (Kılınc¸et al 2006). Before immobilization, 0.01 g of support was equilibrated in 3 mL of 0.05 M phosphate buffer (pH 7) for 20 min at 25C (Kılınc¸et al 2006).…”
Section: Support Preparation and Protease Immobilization Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Before immobilization, 0.01 g of support was equilibrated in 3 mL of 0.05 M phosphate buffer (pH 7) for 20 min at 25C (Kılınc¸et al 2006). Before immobilization, 0.01 g of support was equilibrated in 3 mL of 0.05 M phosphate buffer (pH 7) for 20 min at 25C (Kılınc¸et al 2006).…”
Section: Support Preparation and Protease Immobilization Processmentioning
confidence: 99%
“…Various studies have demonstrated that covalent and noncovalent immobilization of enzymes onto chitosan based supports have a positive effect on the optimum temperature and thermal stability of immobilized biocatalysts (Gomes et al 2004;Kılınc¸et al 2006;Alloue et al 2008;Kumar et al 2009). The optimum temperature of immobilized proteases in the present study, shifted to a higher value than that of free proteases (Fig.…”
Section: Effect Of Immobilization On Optimum Temperature and Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…This was confirmed by the protein assay performed on the aqueous phase (KCl solution). But, the agitation in the collection flask is necessary to keep the capsules (Macario et al 2009;Kılınç et al 2006;Dizge et al 2008;). The immobilization efficiency can be increased by using a hybrid matrix (κ-carrageenan crosslinked with glutaraldehyde).…”
Section: Immobilization Efficiencymentioning
confidence: 99%
“…Meanwhile, marine demosponges of the order Verongiida have been recognized as a renewable source of uniquely pre-structured 3D chitinous scaffolds [20][21][22][23][24][25][26][27][28] which have found applications in tissue engineering [6,21,[29][30][31][32][33][34], drug release [35], the development of hybrid materials [36][37][38][39][40], and environmental science [41,42]. Chitin of invertebrate origin has previously been studied by researchers in protein immobilization as a matrix for the immobilization of enzymes [43][44][45][46][47][48], including lipases [49,50] and papain [51]. However, in this study we investigated the ability of a unique, ready-to-use 3D chitinous scaffold isolated from the marine demosponge Aplysina archeri ( Figure 1) to immobilize laccase as a selected enzyme, and an innovative application of this unique system in the removal of tetracycline by simultaneous adsorption and catalytic conversion.…”
Section: Introductionmentioning
confidence: 99%